Tugas, Peran, Dan Fungsi Guru Dalam Pendidikan - Siti makrifatus Sholehah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Teachers are a crucial element that cannot be overlooked in the teaching and learning process, as they can determine the success or failure of that process. Therefore, in the process of education and instruction, it is essential to have qualified teachers. This means that, in addition to mastering the subject matter and teaching methods, teachers must also understand the fundamentals of education. These educational foundations are extremely important for teachers to know in carrying out their noble duties as instructors or educators. They serve as a means to inspire and motivate students in their learning process. Even if a teacher has excellent mastery of the subject matter, without knowledge of didactic factors, it can create obstacles for students in understanding what the teacher is conveying. On the other hand, teaching experience can actually make it easier for teachers to deliver lessons effectively, especially when supported by the use of appropriate and well-applied teaching methods.